Exploring the concepts of decent work through the lens of SDG 8: addressing challenges and inadequacies - Chigbu, Bianca Ifeoma; Nekhwevha, Fhulu (Frontiers in Sociology, 2023)
Promoting decent work and sustainable economic growth within the framework of Sustainable Development Goal 8 (SDG 8) entails addressing gender inequality, the consequences of market economies, and the role of the informal sector while also considering environmental sustainability. Research on SDG 8 remains limited, often adopting an appraisal perspective, and the concept of decent work within this goal remains relatively unexplored. Additionally, the focus on the challenges and inadequacies of achieving sustainable economic growth through decent work in the context of SDG 8 is insufficient, resulting in significant knowledge gaps. To contribute to filling these gaps, this paper adopts a descriptive and critical review perspective, systematically analyzing 108 journal papers and reports to investigate the concept of decent work within SDG 8. The research addresses the challenges and inadequacies related to decent work embedded in SDG 8. The review reveals that while progress has been made in tackling gender inequality in the labor market, gender bias, income discrepancies, and underrepresentation of women in senior positions persist, hindering inclusive and sustainable economic growth, full and productive employment, and decent work for all -SDG 8. Moreover, SDG 8's focus on inclusive and sustainable development falls short of effectively addressing market economies' structural disparities, insecure working conditions, and exploitative labor practices. Additionally, support for informal sector workers, who lack essential rights such as legal protection and social security, remains insufficient. Ecological destruction is sometimes an unintended consequence of purely market-based labor markets with an emphasis on economic growth, with SDG 8 lacking sufficient integration of environmental sustainability in its framework. The novelty of this study comes from its in-depth, critical, and policy-focused analysis of the ideas around decent employment in the context of SDG 8. The findings underscore the importance of providing fair, safe, and secure employment opportunities to support economic growth and development while upholding workers' rights. In conclusion, we emphasize the crucial role of promoting decent work and sustainable growth in achieving SDG 8's overall objectives, as it directly impacts other SDGs.